2016
DOI: 10.1021/acs.biomac.6b00398
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Based Coacervate of FGF2 Improves Dermal Regeneration by Asserting a Synergistic Role with Cell Proliferation and Endogenous Facilitated VEGF for Cutaneous Wound Healing

Abstract: Effective wound healing requires complicated, coordinated interactions and responses at protein, cellular, and tissue levels involving growth factor expression, cell proliferation, wound closure, granulation tissue formation, and vascularization. In this study, we develop a heparin-based coacervate consisting of poly(ethylene argininylaspartate digylceride) (PEAD) as a storage matrix, heparin as a bridge, and fibroblast growth factor-2 (FGF2) as a cargo (namely heparin-FGF2@PEAD) for wound healing. First, in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 43 publications
3
86
0
3
Order By: Relevance
“…Using ductus ateriosus smooth muscle cells, Wu and colleagues demonstrated that DAPT inhibits cell proliferation by not only inhibiting ERK1/2 and Akt phosphorylation but also by promoting cell cycle arrest in the G0/G1-phase [50]. Collectively, these effects of single stimulation of mCRP, FGF-2 and their combination mCRP with FGF-2 on EC proliferation confirm the theory that growth factors display additive and even synergistic characteristics during early stages of angiogenesis, with the combination of at least two growth factors displaying the highest proliferation rate [51].…”
Section: Discussionmentioning
confidence: 52%
“…Using ductus ateriosus smooth muscle cells, Wu and colleagues demonstrated that DAPT inhibits cell proliferation by not only inhibiting ERK1/2 and Akt phosphorylation but also by promoting cell cycle arrest in the G0/G1-phase [50]. Collectively, these effects of single stimulation of mCRP, FGF-2 and their combination mCRP with FGF-2 on EC proliferation confirm the theory that growth factors display additive and even synergistic characteristics during early stages of angiogenesis, with the combination of at least two growth factors displaying the highest proliferation rate [51].…”
Section: Discussionmentioning
confidence: 52%
“…16 Regranex gel has defined our understanding of growth factor mediated gels for wound healing, and the use of PDGF has been common for many years. [20][21][22][23][24] Other commonly used growth factors include the epidermal growth factor (EGF), [25][26][27][28][29][30][31] fibroblast growth factor (FGF), 21,26,27,32,33 and vascular endothelial growth factor (VEGF). [34][35][36] Table I has a summary of growth factor modified materials and their corresponding strategies for growth factor encapsulation and delivery.…”
Section: Growth Factor Delivery and Microenvironment Recapitulationmentioning
confidence: 99%
“…The FGF2 coacervate had a prolonged release, with only 60% of the growth factor being released by 17 days, which can support long-term delivery of the growth factor to the wound environment. 33 Alternatively, the growth factor can be chemically conjugated to the delivery material hydrogel. Kim et al conjugated the amine terminal of EGF to an aldehyde modified hyaluronate.…”
Section: Growth Factor Delivery and Microenvironment Recapitulationmentioning
confidence: 99%
“…The delivery of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) incorporated nanoparticles from a fibrin based scaffold has shown to promote wound healing in diabetic ulcer [11]. The controlled release of bFGF from a heparin-based coacervate accelerated the wound healing by promoting cell proliferation, re-epithelialization by stimulating secretion of VEGF, and collagen deposition in vivo, in a mouse cutaneous wound model, where the heparin stabilizes the bFGF and prolongs its half-life [12]. The sequential activity of proadrenomedullin N-terminal 20 peptide and bemiparin (a fractionated low-molecular-weight heparin) topically from a bilayered construct favored epithelialization in both ischemic and non-ischemic model [13].…”
Section: Recent Drug-eluting Systemsmentioning
confidence: 99%